Think Pair and Share (TPS) Learning Model in PKn Learning to Improve Communication Class V SDN 101744 Klambir Village - Anggi Ritonga, Windy (Journal of General Education Science, 2023)
This study aims to determine the increase in student communication with the Think Pair and Share (TPS) learning model in PKN Class V SDN 101744 Klambir Village. This research is a Classroom Action Research (CAR). This research was conducted in two cycles. The research subjects were 15 male and 18 female students in class VA at SDN 101744 Klambir Village. The research instrument used in this study was observation sheets of teacher and student activities. The data analysis technique used is descriptive quantitative. Improved student communication can be seen from the acquisition of data in cycle I and cycle II. The results of the analysis show that the average value of teacher activity in cycle I is 46.15% and in cycle II is 92.31%, which means there is a significant increase of 46.16%. The average value of student communication based on the observation sheet in the first cycle was 52.42% and in the second cycle, which was 83.03%, there was a good increase of 30.61%. In the first cycle, there were 2 students who had the ability in the ≤ enough category and in the second cycle, it was shown that there were 32 students who had the ability in the ≤ enough category. Improved communication of class students from cycle I and cycle II, namely as many as 30 students. So that the results of this study can be concluded that there is an increase in student communication by applying the Think Pair and Share learning model at SDN 101744 Desa Klambir. In the first cycle, there were 2 students who had the ability in the ≤ enough category and in the second cycle, it was shown that there were 32 students who had the ability in the ≤ enough category. Improved communication of class students from cycle I and cycle II, namely as many as 30 students. So that the results of this study can be concluded that there is an increase in student communication by applying the Think Pair and Share learning model at SDN 101744 Desa Klambir.